Jejak Perubahan dan Dinamika Kota Malang : Studi Literatur dalam Fotografi - Andhika Putra Herwanto (MAVIS : Jurnal Desain Komunikasi Visual, 2024)
This article documents the role of photography in capturing and analyzing the transformation of Malang City, which celebrates its 110th anniversary in 2024. Through careful literature review, this study identifies the contribution of photography from various genres in enhancing our understanding of the development of infrastructure, social dynamics, and cultural changes in Malang City. The aim of this research is to depict photography not only as a documentation tool but also as an analytical medium that provides profound insights into urban changes from social, economic, and cultural perspectives. The method employed involves content analysis of photographs collected from various sources, including public archives, art exhibitions, and private collections. The findings of this research highlight the importance of photography in recording the history of Malang City's development over time, as well as understanding the impact of these changes on the local community and culture. The implication of this research is to increase appreciation for the documentary and analytical value of photography in the context of urban studies, and to promote the use of photography as a means of reflection and learning for the city's residents.